Labelling of human Wharton's jelly‐derived mesenchymal stem cells with gold nanorods by biomimicry method. (10th August 2021) - Qiyami Hour, Farshid; Shabani, Ronak; Ashtari, Behnaz; Moinzadeh, Alaa; Mehdizadeh, Mehdi
Abstract : Mesenchymal stem cell (MSC)‐based cell therapy can provide opportunities for the treatment of various diseases. However, when used in vivo, these cells should be labelled and monitored by a non‐invasive method during delivery to the desired locations within the body. This study describes a biomimicry method that effectively labels human Wharton's jelly‐derived MSCs (hWJ‐MSCs) with a photoacoustics (PA) contrast agent, gold nanorods (GNRs), without the need for transfection agents (TAs). In this method for cell labelling, the hWJ‐MSCs were co‐incubated with non‐adherent cells isolated from fresh umbilical cord for 2 days immediately before incubation with GNRs. Next, hWJ‐MSCs were labelled with the GNRs at a concentration of approximately 10 10 nanorads/mL (NR/mL) followed by transmission electron microscopy (TEM) and inductively coupled plasma mass spectroscopy (ICP‐MS) to verify their labelling effectiveness. The GNRs‐labelled MSCs prepared by this method had an intracellular gold (Au) concentration of 3.4 ± 0.4 pg/cell, which is an acceptable amount for cell labelling.